(untitled) (Research, Society and Development, 2024)
In Brazil, marital violence is still a common manifestation of violence against women. In this context, although legislative support is necessary, it is still insufficient to reduce the incidence of violence and make women’s rights effective. The health system is an important and safe environment for identifying cases of marital violence and providing care to victims, taking into account the different realities and needs of each woman. In view of this, this study aims to characterize the profile of women victims of marital violence treated in health services in the city of Caruaru-PE in 2019 and 2021. The work was carried out using a cross-sectional methodology and a quantitative approach using secondary data available from the Department of Informatics of the Unified Health System (DATASUS). After including and analyzing the variables of interest, the results point to a profile of conjugal violence for young, brown women with low levels of education, which occurs mainly in the victims’ homes, associated with the recurrence of episodes. Physical violence through beating and threats are the most frequently recorded. This work has therefore made it possible to outline the social factors involved in violence against women, which are important in the context of public health and security.The data from Caruaru is compatible with the Brazilian scenario of violence, vulnerability and inequality to which women are routinely subjected. The limited access to some information made it impossible to take a broader approach to other factors related to female violence.